Cervicomedullary Spinal Cord Injury - Noah King; Andrew Waack; Ethan Kosco; Aastha Bhavsar; Jason Schroeder; Alastair Hoyt (Journal of Orthopaedic Case Reports)
Introduction: Spinal cord injury (SCI) is most common following trauma, typically involving motor vehicle incidents. The clinical prognosis depends on many factors, most importantly the initial grade of injury. Case Report: We present a 26-year-old male who presents to the emergency department after a motor vehicle accident. He sustained significant injuries with an initial Glasgow Coma Scale of 3 and signs of complete SCI. A computed tomography scan demonstrated cervicomedullary transection caused by C6-C7 facet distraction with C6 retrolisthesis on C7. The patient recovered the ability to track with eyes, utilize facial expression, and unilateral trapezius function to command. Neurological recovery was not made despite aggressive treatment. Conclusion: Patients with complete SCI typically have poor outcomes despite aggressive treatment. We present a unique mechanism, treatment, and outcome of a cervicomedullary SCI through C6 retrolisthesis on C7.